Seasonal shifts and complementary use of pollen sources by two bees, a lacewing and a ladybeetle species in European agricultural landscapes. Issue 11 (26th August 2019) - Bertrand, Colette; Eckerter, Philipp W.; Ammann, Lolita; Entling, Martin H.; Gobet, Erika; Herzog, Felix; Mestre, Laia; Tinner, Willy; Albrecht, Matthias
Abstract: Continuous availability of food resources, such as pollen, is vital for many insects that provide pollination and pest control services to agriculture. However, there is a lack of knowledge about the shared or complementary use of floral resources by such species, which hampers more effective landscape management to simultaneously promote them in agroecosystems. Here, we simultaneously quantified pollen use by a bumblebee ( Bombus terrestris ) and a mason bee ( Osmia bicornis ), two bee species recognized as important crop pollinators, as well as a lacewing ( Chrysoperla carnea ) and a ladybeetle species ( Harmonia axyridis ), both common predators of crop aphids, throughout the season in 23 agricultural landscapes in Germany and Switzerland. Pollen diets were more diverse and similar among C. carnea and H. axyridis compared to the two bee species, but all four species shared key pollen types early in the season such as Acer, Quercus, Salix and Prunus . All species exhibited a pronounced shift in pollen sources from primarily woody plants (mainly trees) in spring to primarily herbaceous plants in summer. The majority of pollen (overall ≥64%) came from non‐agricultural plants even in crop‐dominated landscapes. Synthesis and applications . Our results highlight the importance of trees as pollen sources for many insect species, particularly early in the season. Our findings support incentives that promote heterogeneous agricultural landscapes including both woody and herbaceous semi‐natural habitats, ensuring phenological complementarity of floral resources for insect species that can provide pollination and pest control services to agriculture. The identified key plant species can help to design and optimize agri‐environment schemes to promote these functionally important insects. Abstract :